The effect of animal food match play therapy on anxiety levels of children aged 5-6 years experiencing hospitalization - Desta Charolyn Sose; Santi Oktaviani; Ida Subardiah (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Hospitalization in preschool children often causes anxiety due to unfamiliar environments, medical procedures, and separation from parents. Anxiety that is not managed properly may affect children's psychological well-being and recovery process. One non-pharmacological intervention that can be used to reduce anxiety in children is play therapy. Purpose: This study aimed to determine the effect of Animal Food Match play therapy on anxiety levels of children aged 5–6 years who experience hospitalization. Method: This study used a quantitative research design with a pre-experimental approach using a one-group pretest-posttest design. The research was conducted in the pediatric inpatient ward of Imanuel Hospital, Bandar Lampung. The sample consisted of 30 children aged 5–6 years who experienced hospitalization and were selected using Porpusive sampling technique. Data were collected using an anxiety observation questionnaire. Data analysis was performed using the Wilcoxon Signed Rank Test with a significance level of 95% (α = 0.05). Results: The results showed that the mean anxiety score before intervention was 1.23 and decreased to 0.03 after the intervention, with a mean difference of 1.20. The Wilcoxon test showed a Z value of -5.108 and a p-value of 0.001 (p < 0.05), indicating a significant difference between pre-test and post-test scores. Conclusion: Animal Food Match play therapy has a significant effect in reducing anxiety levels in children aged 5–6 years who experience hospitalization. Suggestion: Nurses are recommended to apply play therapy as a nursing intervention to reduce anxiety in hospitalized children.